Hydrogen and Fuel Cells 2017
DOI: 10.18690/978-961-286-054-7.15
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Profit Potential of Energy Storage in a Car Park Using Electrolysis, Hydrogen Storage and Fuel Cell Electric Vehicles

Abstract: The aim of SEEP2017 is to bring together the researches within the field of sustainable energy and environmental protection from all over the world.The contributed papers are grouped in 18 sessions in order to provide access to readers out of 300 contributions prepared by authors from 52 countries.We thank the distinguished plenary and keynote speakers and chairs who have kindly consented to participate at this conference. We are also grateful to all the authors for their papers and to all committee members.We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We used solar and wind energy as well as hydrogen and fuel cell EVs (FCEVs) to provide backup and balancing power. We also demonstrated that with optimal scheduling, it is possible to minimize the electricity import from an external network in a microgrid [12]- [17], and we showed that investing in such energy systems can be profitable for all parties involved [18].…”
Section: Development Of the Capp Smart Citymentioning
confidence: 74%
“…We used solar and wind energy as well as hydrogen and fuel cell EVs (FCEVs) to provide backup and balancing power. We also demonstrated that with optimal scheduling, it is possible to minimize the electricity import from an external network in a microgrid [12]- [17], and we showed that investing in such energy systems can be profitable for all parties involved [18].…”
Section: Development Of the Capp Smart Citymentioning
confidence: 74%
“…This was done within the Car as Power Plant project which entails a vision of an integrated sustainable energy and mobility system, based on renewable energy sources, hydrogen as an energy carrier and FCEVs [6]. A main business case related to the Car as Power Plant concept is that of the Car Park as Power Plant (CPPP), which consists of the aggregation of FCEVs parked in a car park into a 'virtual power plant' to produce electricity and feed it into the power grid [28]. This work elaborates on this existing concept and brings new insights on the use of FCEVs for frequency reserves.…”
Section: Fuel Cell Electric Vehicles and V2gmentioning
confidence: 99%